PENDIDIKAN ISLAM ANTI RADIKALISME MELALUI NADHAM (Telaah Kitab Shifa’ al-Ummah karya KH. Taufiqul Hakim Bangsri Jepara) - Rohman, Fathur (TADRIS: Jurnal Pendidikan Islam, 2018)
Several studies have shown that radicalism now at an alarming level. One of the indicator is the inclusion of the teaching radicalism to various educational institutions. Responding to this phenomenon, PP. Darul Falah Bangsri Jepara published a book entitled Syifa’ al-Ummah. This book is written by KH. Taufiqul Hakim in the form of a nadham that discuss radicalism from the point of view of Islamic teachings. Based on the description, this article will answer two problems. First, the anti-radical values expressed in the nadham Syifa’ al-Ummah. Secondly, the reason for the use of nadham in presenting anti-radicalism values. Therefore, this study uses content analysis techniques to find out the massages contained in the text of the book, Syifa al-Ummah. From the results of this study can be seen that the values of anti-radicalism in the book, Syifa’ al-Ummah among others: Islam is a religion of grace, Islam prohibits acts of terror, the meaning of jihad, change of munkar gradually, and government in Islam. The writing of the book in the form of nadham aims to facilitate the reader in memorizing and remembering the material presented.